Islam and Social Media in Indonesia: A Study of the Living Qur'an and Hadith in the Film “Ruqyah: The Exorcism” - Ihsan Nurmansyah; Sherli Kurnia Oktaviana (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2022)
This paper discusses the phenomenon of the living qur'an and hadith on the ruqyah scene in the film“Ruqyah: The Exorcism” which MD Pictures, Dee Company and Pichouse Films produced in 2017. The film “Ruqyah: The Exorcism” is a religious horror genre film where in each scene there is a phenomenon of the living qur'an and hadith in the form of the use of verses. Al-Qur'an and Hadith of the Prophet in the ruqyah ritual. Therefore, to find out the functional reception of the verses of the Qur'an and the hadith of the Prophet used in the film